Counselor Performance Test Instrument: Validity, Reliability, and Implications for Group Guidance Services - Budi Purwoko; Ach. Sudrajad Nurismawan (Mimbar Ilmu, 2023)
The development of counselor performance assessment instruments, especially for group guidance services, is still being developed independently by each higher education institution. It tends to be non-standard and not entirely in line with the need to create counselor competency in implementing school group guidance services. This research aims to create a performance test instrument for group guidance services for school counselors that is valid and reliable by adapting the development model from Borg & Gall at three stages of development. By involving 5 subjects as testers for the acceptability of performance instruments, namely 2 lecturers and 3 school counselors. Thirty-nine construct validity and reliability testing subjects consist of 2 lecturers, 12 school counselors, and 20 practical students. This development resulted in a set of counselor performance assessment instruments in group guidance services consisting of 13 statement instrument items on the planning aspect and 27 on the practice aspect, tested as valid and reliable based on SPSS 26 analysis. Furthermore, experts and users have also validated the assessment instrument by meeting acceptability criteria (applicable, feasible, and appropriate). Thus, it can be concluded that the counselor performance test instrument product in group guidance has met the development objectives and can be used for assessment in the planning and practice of group guidance services in schools or clinical counseling supervision activities.